2018
DOI: 10.3390/ijms19103203
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Arterial Hypertension and Hereditary Haemorrhagic Telangiectasia

Abstract: Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant inherited disease characterised by multisystemic vascular dysplasia. Heritable pulmonary arterial hypertension (HPAH) is a rare but severe complication of HHT. Both diseases can be the result of genetic mutations in ACVLR1 and ENG encoding for proteins involved in the transforming growth factor-beta (TGF-β) superfamily, a signalling pathway that is essential for angiogenesis. Changes within this pathway can lead to both the proliferative vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 86 publications
(114 reference statements)
0
47
0
4
Order By: Relevance
“…However, the recurring and progressive nature of the disease continues to make HHT a highly debilitating disorder associated with life-threatening sequelae. Several disease-modifying therapies have been proposed in preclinical models, and some of them are currently being investigated in clinical trials (49). Notably, Tac was found to be associated with Smad1/5/8-activating properties in ECs and showed some efficacy in reducing pathology in HHT (32) and PAH (37) models and patients (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…However, the recurring and progressive nature of the disease continues to make HHT a highly debilitating disorder associated with life-threatening sequelae. Several disease-modifying therapies have been proposed in preclinical models, and some of them are currently being investigated in clinical trials (49). Notably, Tac was found to be associated with Smad1/5/8-activating properties in ECs and showed some efficacy in reducing pathology in HHT (32) and PAH (37) models and patients (50-52).…”
Section: Discussionmentioning
confidence: 99%
“…More cases of HHT and pulmonary hypertension were reported among patients with ACVRL1 mutations than among patients with ENG mutations (5). Previous studies, that did not include genetic information about ACVRL1 mutations, found that HHT and pulmonary hypertension patients had a higher mortality, and died due to cardiac diseases associated with pulmonary hypertension, sepsis, and major bleeding related to HHT (6,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary hemorrhagic telangiectasia (HHT) is an autosomal dominant inherited vascular disease that occurs in approximately 1 in 10,000 people worldwide (1)(2)(3); and 85-95% of cases are caused by pathogenic variants of activin A receptor type II-like 1 (ACVRL1) and endoglin (ENG) (1,4). The ACVRL1 and ENG genes encode members of the transforming growth factor (TGF)-β receptor family, and play important roles in different cellular processes, including proliferation, migration, and apoptosis (5). HHT is characterized by arteriovenous malformation in the lung, liver, and brain, and recurrent epistaxis due to telangiectasia.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recurring and progressive nature of the disease continues to make HHT a highly debilitating disorder associated with life-threatening sequelae. Several disease-modifying therapies have been proposed in preclinical models and some of them are currently being investigated in clinical trials (49). Notably, Tac was found to be associated with Smad1/5/8 activating properties in ECs and showed some efficacy in reducing pathology in HHT (32) and PAH (37) models and patients (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%